Analysis of three-dimensional bending deformations and failure of wet and dry laminates. (15th November 2020) - Jain, D.; Zhao, Y.Q.; Batra, R.C.
Abstract: For given mechanical properties of the fiber and the matrix, and their volume fractions, we first numerically, using the finite element method, find values of the elastic moduli and the diffusivity of the homogenized unidirectional (UD) lamina. However, values of material parameters appearing in the Hashin failure criteria for a lamina and in the cohesive zone model for simulating delamination between adjacent plies, the coefficient of swelling (or hygral expansion), and of the reduction in values of parameters upon full saturation with water are taken from the literature. Using these values, we analyze 3-dimensional hygro-mechanical deformations of dry and fully saturated UD and cross-ply (CP) laminates for a 3-point bending configuration, and delineate differences in failure mechanisms of dry and wet laminates. It is found that, at full saturation, the hygral stresses are negligible in UD laminates but alternate between compressive and tensile values of large magnitude in the CP laminate. Furthermore, the hygral stresses are found to suppress failures in some regions but facilitate in other parts of the laminates. During displacement controlled simulations, the maximum load at the mid-span of wet laminates is found to be about 30% less than that for the corresponding dry laminates, delamination induced between adjacent plies of a laminate causes noticeable sliding between them, and warping near the laminate corners.